Utilization of Booklet Media in Providing Information Services for Students' Understanding of Career Choice - Suriatie, Mimi; Rizka, Ramadhanti; Sangalang, Oktamia Karuniaty (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study is an experimental research using the "One Group Pre-Test and Post-Test Design." The population of the study consisted of all 35 students in class XII MIPA 4 at MAN Kota Palangka Raya. The study used a sample selected through purposive sampling, a non-random sampling technique based on specific criteria or objectives. In this case, the targeted objective was students who were categorized as having low understanding of career decision-making. According to Arikunto (2017), if the subject number is fewer than 100, the entire population can be used as the sample. Therefore, the researcher used the entire population as the sample, since it was fewer than 100 students. The main data collection technique used by the researcher was a questionnaire distributed to assess the improvement in students’ understanding of career choices after being given informational services. Data analysis was conducted using parametric statistics through the Kolmogorov-Smirnov test, with the help of the SPSS version 25 statistical software, since the data was normally distributed. The researcher drew conclusions based on statistical results. The research findings showed that the result of the t-test using the Paired Sample t-Test was sig. 0.000 < 0.05, and the calculated t-value (tcount) was greater than the table value (ttable), namely 10.822 > 2.052. Thus, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. Therefore, it can be concluded that the use of booklet media can assist students in understanding career choices in class XII MIPA 4 at MAN Kota Palangka Raya.